Ultrastructural changes in burnt dental tissue revealed by synchrotron x-ray scattering - Sui, T; Sandholzer, M; Baimpas, N; Landini, G; Damien, W; Lumley, P; Korsunsky, A (2013)
The investigation of ultrastructural alterations of skeletal hard tissue exposed to thermal treatment has been proven to be crucial to obtain a reliable estimation of thermal exposure for forensic and archaeological study. However, there is only limited data on the heat-induced compositional and structural alterations of dental tissue. Visualizing and understanding the internal architecture of these materials is a challenging task that cannot be readily accomplished by conventional microscopy methods alone. We describe some experimental arrangements making use of synchrotron X-ray beams that shed light on the ultrastructure alterations of dental tissue. In particular, SAXS was used to investigate the alterations in thermally treated dental tissues, aiming at probing the ultrastructural changes of hydroxyapatite (HAp). The information about the internal architecture (the variation of crystalline size and the orientation of HAp nano-particles) of dental tissues was collected, providing a basis for estimating the maximum temperature exposure of forensic dentine samples.